1998
DOI: 10.2114/jpa.17.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sweet Suppressing Agent on Gustatory Brain Evoked Potentials Generated by Taste Stimuli.

Abstract: Abstract.A measurement system was employed to detect gustatory evoked potentials from human scalp by stimulus of a taste solution with the use of a laser beam device. The evoked potentials for four taste qualities (i.e., sweet-sucrose, salty-sodium chloride, sour-tartaric acid, and bitter-quinine-HCl) were measured before and after treatment with a sweet suppressing agent (i.e., gymnema sylvestre extract) to the tongue of a human. The solution was given to the chorda tympani nerve located 20 mm from the apex o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 30 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Mizoguchi et al (2002) reported the N1 deflection for salt at a latency of 256 ms in the region of the cranial vertex. Early ERP studies which focused on ERP deflection (i.e., Min and Sakamoto (1998), and Franken et al (2011)) were hindered by the gustatory and tactile stimulation, which influenced their interpretation of the reported results. These studies were not concentrated on brain regions where deflection occurred, but rather on the difference in potential between different tastes.…”
Section: Eeg Studies Related To Swallowingmentioning
confidence: 99%
“…Mizoguchi et al (2002) reported the N1 deflection for salt at a latency of 256 ms in the region of the cranial vertex. Early ERP studies which focused on ERP deflection (i.e., Min and Sakamoto (1998), and Franken et al (2011)) were hindered by the gustatory and tactile stimulation, which influenced their interpretation of the reported results. These studies were not concentrated on brain regions where deflection occurred, but rather on the difference in potential between different tastes.…”
Section: Eeg Studies Related To Swallowingmentioning
confidence: 99%